2014
DOI: 10.1590/1678-6514
|View full text |Cite
|
Sign up to set email alerts
|

Fontes de amido no concentrado de bovinos superprecoces de diferentes classes sexuais

Abstract: Fontes de amido no concentrado de bovinos superprecoces de diferentes classes sexuais

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[ 42 ] observed a 16 % increase in weight gain when providing exogenous enzymes. Cattle supplemented with an amylase-based enzymatic complex [ 43 ] concluded that starch from corn caused improvements in subcutaneous fat thickness in feedlot super-early steers. Another point that we can observe was the concentration of mineral matter, which was higher in the meat of cattle that consumed the enzymatic combination T4-BLEND+AMIL, but it was not evaluated which minerals were deposited in the muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] observed a 16 % increase in weight gain when providing exogenous enzymes. Cattle supplemented with an amylase-based enzymatic complex [ 43 ] concluded that starch from corn caused improvements in subcutaneous fat thickness in feedlot super-early steers. Another point that we can observe was the concentration of mineral matter, which was higher in the meat of cattle that consumed the enzymatic combination T4-BLEND+AMIL, but it was not evaluated which minerals were deposited in the muscle tissue.…”
Section: Discussionmentioning
confidence: 99%